2016
DOI: 10.1097/bcr.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Oxandrolone Improves Lung Function in Pediatric Burned Patients

Abstract: Pulmonary dysfunction is a significant contributor to morbidity and mortality in the pediatric burned population. We have previously reported that the administration of a synthetic testosterone derivative, oxandrolone, significantly reduced hypermetabolism, and significantly increased height percentile, bone mineral content, lean body mass, and strength in pediatric burned patients. Objective We hypothesize that the administration of oxandrolone will improve pulmonary function in burned pediatric subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…26 Although the duration of oxandrolone administration in adults was short, in children, the long-term administration of oxandrolone for up to one year postburn improved lean mass, lung function, and both bone mineral density and bone mineral content. 272930 The benefits of long-term oxandrolone administration persisted well beyond the duration of therapy in severely burned children as well. 31,32…”
Section: Introductionmentioning
confidence: 99%
“…26 Although the duration of oxandrolone administration in adults was short, in children, the long-term administration of oxandrolone for up to one year postburn improved lean mass, lung function, and both bone mineral density and bone mineral content. 272930 The benefits of long-term oxandrolone administration persisted well beyond the duration of therapy in severely burned children as well. 31,32…”
Section: Introductionmentioning
confidence: 99%
“…[61,62] Markers of lung function, such as maximum voluntary ventilation and maximum expired ventilation are also improved by long-term oxandrolone therapy. [63] Research in adult burn patients shows that oxandrolone, combined with adequate nutritional intake, reduces weight loss and daily nitrogen loss in the recovery phase of severe burn injuries by decreasing muscle protein breakdown. [64,65] It has also been demonstrated that oxandrolone improves the rehabilitation of these patients by increasing weight gain up to three times faster compared with nutritional support alone.…”
Section: Recovery After Acute Critical Illnessmentioning
confidence: 99%
“…[51][52][53][54][55][56][57] In the recovery phase oxandrolone therapy, physical exercise and adequate nutritional intake have been shown to reverse growth arrest and improve both body composition and lung function. [59][60][61][62][63][64][65] Previous studies addressing the effect of testosterone on mechanical ventilation showed conflicting and statistically insignificant results. [51,56,57] No study has identified testosterone therapy alone as the solution to treat ICU-acquired weakness.…”
Section: • Multicentre Observationalmentioning
confidence: 99%
“…Oxandrolone is a synthetic dihydrotestosterone derivative that, in the severely burned, decreases length of stay (58), improves lean body mass and muscle accretion (44, 58), increases bone mineral content and bone mineral density (45), enhances wound healing, accelerates growth rate (46), decreases the risk of osteoporosis (46), reduces protein breakdown (59), improves muscle strength (44), and improves lung function (48). In burned adults, administration of oxandrolone within 7 days of injury decreased mortality compared to untreated controls (60).…”
Section: Modulating the Hypermetabolic Responsementioning
confidence: 99%